PROSES PENETAPAN KRITERIA KETUNTASAN MINIMAL (KKM) PADA MATA PELAJARAN EKONOMI KELAS X DI SMA SE-KECAMATAN LUBUK KILANGAN KOTA PADANG - Wahyuni, Sri; Areva, Desi; Dahen, Lovelly Dwinda (Jurnal Ipteks Terapan, 2014)
This study aims to look at how the process of determining the minimum completeness criteria (KKM) High School districts namely Lubuk Kilangan 14 SMA N SMA Semen Padang and Padang and What are the obstacles faced in the Determination of minimum completeness criteria (KKM). This study uses kualaitatif. This research informants are teachers, principals, and representatives of the existing curriculum at the high school and high school N 14 Semen Padang Padang using Snawball sampling. Data were collected using observation, interview and documentation. The results of the study found: Minimum completeness criteria setting process (KKM) is: Principal KKM has set a minimum that must be achieved by the subject teachers, Having known the value of the minimum KKM subject teachers at a workshop convened to determine the KKM for Economic Subjects class X which starts from Standard competence, basic competence to later demoted to the indicator. So after KKM determined subject teachers reported the results of the meeting to the representative of the curriculum, the curriculum report to the Vice Principal, principal chief engineer reported the results to the Department of Education and to the Office of Padang province, then disseminated to students and parents in the form of student learning lembarhasil. While the obstacles encountered in the determination of this KKM is: Time penentukan KKM is not planned in accordance with the existing circumstances, When the teacher determines the minimum value of completeness (KKM) is too high then the students do a lot of remedial, When the teacher determines the minimum value of mastery is too low then the student will difficult to get into college. Doi:Â 10.22216/jit.2014.v8i3.6